The Annalysis of Distance Covered, Heart Rate, and Body Fluid Loss in Every Position of Football Player - Muhammad Yusuf Rojali Rahmatillah; Eka Nugraha; Hamidie Ronald Daniel Ray (JUARA : Jurnal Olahraga, 2019)
The aim of this study was to analyze the extent of distance, heart rate, and loss of body fluids in various positions in Indonesian professional soccer players as the basic material for planning an exercise program Method: this study uses a quantitative descriptive method. The sample of this study is the 11-player BUFC team in the 2019 Presidential Cup match against SPFC using a purposive sampling technique approach. The results of this study show the distance covered the most reached External Midfielder 10.421 m, the highest Heart Rate Maximum reached Central Midfielder 200 bpm, Average heart highest rate External Defender 165 bpm, the biggest loss of body fluids Central Midfielder 0.9 %. The conclusion of the research based on the results of data analysis shows that Central Midfielder, External Midfielder, and External Defender are the positions that do the most distance (Distance Covered), maximum maximum heart rate, highest average heart rate, and the most loss of body fluids.